ISLAM NUSANTARA : TELAAH METODOLOGIS DAN RESPONS TERHADAP KHILAFATISME DI INDONESIA - Fauzi, M. Nur (JURNAL ISLAM NUSANTARA, 2019)
This library research discusses the paradigm and methodology of Islam Nusantara and it’s response to the idea of islamic state or called khilafah islamiyah in Indonesia. As library research this paper tries to explore several problems; firstly, how the paradigm of Islam Nusantara; secondly, how the methodology of Islam Nusantara; and thirdly, how it’s response to the idea of islamic state or called khilafah islamiyah. From these purposes could be mapping and solving several problems in our society. However, the emphasis on the methodology of Islam Nusantara is an urgent need as the basis of typology. Islam Nusantara proposes a thesis that Islam should be understood contextually and historically. In addition, this article also describes how Islam Nusantara through manhaj al-fikr or its thinking methodology response to the idea of a literal-scripturalist or khilafah islamiyah in Indonesia. From this we get a conclusion that strengthening the base of Islam Nusantara through the formulation of appropriate methodology will result in a comprehensive understanding of Islam and compatible with the era.